The Effect of Inflation, Exchange Rates and Third-Party Funds on Financing to Deposit Ratio (FDR) at Sharia Commercial Banks in 2019-2023 - Latviani Z, Devira; Setiawan, Iwan (Indonesian Journal of Economics and Management, 2025)
This study aims to analyze the influence of inflation, exchange rates, and third-party funds on the Financing to Deposit Ratio (FDR) in Sharia Commercial Banks in Indonesia during the 2019–2023 period. The research addresses the problem of fluctuating macroeconomic conditions—particularly inflation and exchange rate volatility—which affect the liquidity and intermediation function of Islamic banks. Additionally, the role of third-party funds (DPK), as the main source of Islamic bank financing, is explored to understand its effect on FDR. This study adopts a quantitative research method using secondary data sourced from the annual financial reports of eight Islamic Commercial Banks, alongside data from the Central Statistics Agency and Bank Indonesia. The sample was selected through purposive sampling. The analysis was performed using multiple linear regression with IBM SPSS Statistics 30. The results show that inflation and exchange rate fluctuations have a negative and significant effect on FDR, indicating that macroeconomic instability reduces banks’ ability to efficiently distribute financing. Conversely, third-party funds have a positive and significant impact, confirming their critical role in supporting financing activities. Simultaneously, all three variables significantly influence the FDR, with a coefficient of determination of 47.5%, suggesting that nearly half of the variation in FDR can be explained by these factors. In conclusion, the FDR of Islamic banks is sensitive to macroeconomic indicators. Effective management of inflation and exchange rate risks, along with optimized fund mobilization, is essential for maintaining financial stability. The findings offer valuable insights for regulators and Islamic bank managers in enhancing risk management and strategic plannin.